Case Report: Step-by-step procedures for total intracorporeal laparoscopic kidney autotransplantation in a patient with distal high-risk upper tract urothelial carcinoma - Wu, Guohao; Li, Haomin; Li, Junqiang; Chen, Mubiao; Xie, Lishan; Luo, Huilan; Chen, Zhihui; Ye, Dongming; Lai, Caiyong (Frontiers in Oncology, 2023)
This case-based discussion describes a 47-year-old man who presented to the emergency department with right abdominal pain and a new onset of painless hematuria two weeks earlier.Urine cytology test results were considered to be urothelial carcinoma.A computed tomographic urogram（CTU）showed a filling defect in the lower right ureter with right hydronephrosis.A lymphadenopathy and any signs of a metastatic disease were absent on CTU. Cystoscopy appeared normal.Creatinine was also normal before surgery.After discussion of the treatment options, the patient chose to have a 3D totally intracorporeal laparoscopic kidney autotransplantation,bladder cuff excision, and segmental resection of the proximal two-thirds of the ureter based on the membrane anatomy concept.After more than one year of follow-up,the patient was well and had no further hematuria, there was no evidence that the disease recurrence was found in surveillance cystoscopy and CTU examination.Therefore,it is reasonable to assume that kidney-sparing surgery may be considered for patients with carefully selected high-grade upper tract urothelial carcinoma.